A CLINICAL STUDY OF VARIOUS PRESENTATION AND TREATMENT OUTCOME OF VARICOCELE - Dr. Rajesh T.S.; Dr. Surendra Mohan H.M; Dr. Prasad H.L; Dr. Rama Krishna M. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Backgrounds Despite being first described two thousand years ago, the varicocele remains a controversial multifaceted disease process with numerous biological consequences including infertility, hypogonadism, and chronic orchidalgia. Despite a high prevalence amongst asymptomatic fertile men, varicoceles paradoxically also represent the most common correctable cause for male infertility. ObjectivesThe objective of the study is to study the various clinical presentation and treatment outcome of varicocele.MethodsA prospective clinical study was undertaken at K.R. Hospital attached to Mysore Medical College and Research Institute, Mysore to observe and document the various clinical presentation and treatment outcome of varicocele.ResultsVaricocele was more prevalent among the 3rd decade in our study. Infertility was the most prevalent presentation (46%) followed by scrotal pain / discomfort (44%) among study population. 10% of our study population was asymptomatic. In our study, on USG of scrotum, 40 patients (80%) had Grade 4 varicocele, 8 (16%) had Grade 3 and 2 patients (4%) had grade 2 varicocele and 42 patients had abnormal semen analysis. On comparison of USG grading with the semen analysis, 81% of the patients with abnormal semen analysis had Grade 4 varicocele.(p